Adult Living Donor Versus Deceased Donor Liver Transplant (LDLT Versus DDLT) at a Single Center: Time to Change Our Paradigm for Liver Transplant. Issue 3 (September 2019) - Humar, Abhinav; Ganesh, Swaytha; Jorgensen, Dana; Tevar, Amit; Ganoza, Armando; Molinari, Michele; Hughes, Christopher
Abstract : Objective: The aim of this study was to compare outcomes between living donor liver transplant (LDLT) and deceased donor liver transplant (DDLT) at a single center to demonstrate the advantages of LDLT and provide justification for the increased utilization and application of this procedure. Summary of Background Data: LDLT comprises a very small percentage of all liver transplants performed in the United States, this despite its advantages and a shortage of the availability of deceased donor organs. Methods: A retrospective review of all adult LDLT (n = 245) and DDLT (n = 592) performed at a single center over 10 years (2009–2019), comparing survival outcomes by Kaplan-Meier analysis and comparing other measures of outcome such as recovery times, complications, costs, and resource utilization. Results: Patient survival outcomes were superior in LDLT recipients (3-year 86% vs 80%, P = 0.03). Other outcomes demonstrated shorter length of hospital stay (11 vs 13 days, P = 0.03), less likelihood of intraoperative blood transfusion (52% vs 78%, P < 0.01), and less likelihood of need for posttransplant dialysis (1.6% vs 7.4%, P < 0.01). Early reoperation and biliary/vascular complication rates were similar. Hospital costs related to the transplant were 29.5% lower for LDLT. Complications in living donors were acceptable with no early or late deaths, 3-month reoperation rate of 3.1%, and overall complication rate of 19.5%. Given its advantages, we have expanded LDLT—in 2018, LDLT comprised 53.6% of our transplants (national average 4.8%), and our transplant rate increased from 44.8 (rate per 100-person years) in 2015 to 87.5 in 2018. Conclusions: LDLT offers advantages over DDLT including superior outcomes and less resource utilization. The time has come to change the paradigm of how LDLT is utilized in this country.